2020
DOI: 10.1093/milmed/usaa014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a 4-hour Introductory eFAST Training Intervention Among Ultrasound-Naïve U.S. Military Medics

Abstract: Introduction Advances in the portability of ultrasound have allowed it to be increasingly employed at the point of care in austere settings. Battlefield constraints often limit the availability of medical officers throughout the operational environment, leading to increased interest in whether highly portable ultrasound devices can be employed by military medics to enhance their provision of combat casualty care. Data evaluating optimal training for effective medic employment of ultrasound is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Fluid volumes from 100ml collected at the abdominal level (hemoperitoneum), can be detected with ultrasound assessment, and at the thoracic level from 5ml can be observed (hemothorax and pleural effusion), however, this is directly proportional to the operator's capacity (Monti & Perreault, 2020).…”
Section: Protocol: Fastmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluid volumes from 100ml collected at the abdominal level (hemoperitoneum), can be detected with ultrasound assessment, and at the thoracic level from 5ml can be observed (hemothorax and pleural effusion), however, this is directly proportional to the operator's capacity (Monti & Perreault, 2020).…”
Section: Protocol: Fastmentioning
confidence: 99%
“…To facilitate the visualization of free fluid in the pelvic cavity, it is ideal for the bladder to be filled with fluid or for the bladder to be distended; and when there is free fluid, it is located in the posterior or upper part of the bladder or uterus in the case of women (Monti & Perreault, 2020). This can be interrupted in the detection of free fluid when the patient is previously placed a bladder catheter and the bladder is completely emptied, and if there is a compromise of the acoustic window it can only be detected if it occupies large amounts of free fluid (Carrera Sieiro JC et al, 2020).…”
Section: • Techniquementioning
confidence: 99%
“…Ultrasound learners can now develop image acquisition, interpretation, and procedure skills through a variety of simulation technologies. [ 7 , 88 , 92 93 94 95 96 97 98 99 100 101 102 103 104 ] Additional ultrasound simulation applications have been developed to further assess how well learners can integrate ultrasound findings into clinical decision-making. [ 99 , 105 ]…”
Section: The Role Of Ultrasound Simulationmentioning
confidence: 99%
“…24 Previous research has shown emergency medical technicians can be trained in trauma sonography after a brief training intervention to achieve results comparable to physicians. [25][26][27] Participants performed all FASTs on an US phantom model, not a live human model or an actual trauma patient. This limits generalizability as patient factors such as obesity, difficult sonographic windows, movement, pain, altered mentation, and several others may complicate FAST performance.…”
Section: Limitationsmentioning
confidence: 99%